2005
DOI: 10.1897/04-250r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genotoxicity and contaminant exposure: Evidence of genomic instability in the marsh frogs (rana ridibunda) of sumgayit, azerbaijan

Abstract: The wetlands of Sumgayit in the Azerbaijan Republic contain complex mixtures of contaminants, including polycyclic aromatic hydrocarbons (PAHs), mercury, organochlorine pesticides, and polychlorinated biphenyls. Marsh frogs (Rana ridibunda) were collected from several contaminated wetlands within the city as well as from two reference sites outside the city. Sediment samples revealed heterogeneous patterns of PAH and mercury concentrations throughout Sumgayit, with the highest levels occurring east of the Sumg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Amphibians exhibit a variety of adverse effects from environmental exposure and can be used as sentinel species when investigating environmental risks at contaminated sites. [29][30][31] Maselli et al used frogs to evaluate DNA damage related to pollution in Naples and neighboring Provinces. Twenty frogs were sampled from several sites of the Campania Region, including areas in the close proximity of dumping sites (both legal and illegal), sites influenced by intensive farming and uncontaminated sites.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Amphibians exhibit a variety of adverse effects from environmental exposure and can be used as sentinel species when investigating environmental risks at contaminated sites. [29][30][31] Maselli et al used frogs to evaluate DNA damage related to pollution in Naples and neighboring Provinces. Twenty frogs were sampled from several sites of the Campania Region, including areas in the close proximity of dumping sites (both legal and illegal), sites influenced by intensive farming and uncontaminated sites.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Oil production, as well as the chemical and manufacturing plants of Sumgayit, has left the Apsheron Peninsula of Azerbaijan with a complex mixture of environmental contaminants. Environmental degradation and contamination in Azerbaijan, specifically in Sumgayit, have been explored recently (Andruchow 2003; Bickham et al 2003; Matson et al 2005a, 2005b; Shelton 2003; Swartz et al 2003). Elevated levels of numerous potentially mutagenic contaminants, including polycyclic aromatic hydrocarbons (PAHs), mercury, polychlorinated biphenyls, and organochlorines, have been documented in wildlife, sediments, and soils from Sumgayit and the capitol city of Baku (Bickham et al 1998; Matson et al 2005a, 2005b; Swartz et al 2003).…”
mentioning
confidence: 99%
“…There is no evidence to suggest that either of these localities is generating new mutations in mosquitofish as was concluded for WTP by Matson et al (2006) for marsh frogs. Moreover, Matson et al (2005b) showed evidence of somatic chromosomal mutations in frogs from both CAP and WTP. Rather, for mosquitofish it appears that site 108, a wetland at the edge of the industrial sector, is the best candidate for the origin of all or most of the de novo mutations from which the rare and low frequency heteroplasmic conditions are derived.…”
Section: Discussionmentioning
confidence: 99%
“…Matson et al (2005a) measured sediment PAH and Hg levels from the wastewater treatment plant in Sumgayit taken in 2002 and showed that PAH and Hg levels had dropped significantly between 2002 and 1996, and this was associated with visible improvement in the habitat documented by photographs. Matson et al (2005b) reported contaminant levels in sediment at multiple sites in Sumgayit and as well reported tissue contaminant levels in frogs, all taken in 2001. Biomarker studies of turtles and frogs documented genetic impacts on somatic tissues (Matson et al 2005a, b;Swartz et al 2003).…”
Section: Introductionmentioning
confidence: 99%